2006
DOI: 10.1890/0012-9658(2006)87[1684:wdnhtm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Warmer Does Not Have to Mean Sicker: Temperature and Predators Can Jointly Drive Timing of Epidemics

Abstract: Ecologists and epidemiologists worry that global warming will increase disease prevalence. These fears arise because several direct and indirect mechanisms link warming to disease, and because parasite outbreaks are increasing in many taxa. However, this outcome is not a foregone conclusion, as physiological and community-interaction-based mechanisms may inhibit epidemics at warmer temperatures. Here, we explore this thermal-community-ecology-based mechanism, centering on fish predators that selectively prey u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 53 publications
6
101
1
Order By: Relevance
“…For 14 parasite isolates classified by morphology as fungi and originating from five locations in Europe and three locations in the United States (Table 1), only one sequence variant (referred to below as METS) was detected by direct sequencing of SSU, ITS, and partial LSU regions. Because the reference parasite isolates from the United States had been described previously as isolates belonging to Metschnikowia bicuspidata (a yeast in the family Hemiascomycetes [12,21]), the sequences obtained were aligned with several published sequences of Hemiascomycetes. Neighbor-joining and parsimony analyses showed that the SSU, ITS, and partial LSU sequences of the isolated fungal parasite taxon METS are clearly distinct from the SSU, ITS, and partial LSU sequences of several M. bicuspidata isolates that have been published previously (bootstrap support, Ͼ90%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For 14 parasite isolates classified by morphology as fungi and originating from five locations in Europe and three locations in the United States (Table 1), only one sequence variant (referred to below as METS) was detected by direct sequencing of SSU, ITS, and partial LSU regions. Because the reference parasite isolates from the United States had been described previously as isolates belonging to Metschnikowia bicuspidata (a yeast in the family Hemiascomycetes [12,21]), the sequences obtained were aligned with several published sequences of Hemiascomycetes. Neighbor-joining and parsimony analyses showed that the SSU, ITS, and partial LSU sequences of the isolated fungal parasite taxon METS are clearly distinct from the SSU, ITS, and partial LSU sequences of several M. bicuspidata isolates that have been published previously (bootstrap support, Ͼ90%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown both in the field and under controlled laboratory conditions that parasites have a substantial impact on Daphnia fitness (7,21,52). Parasiteinduced reductions in Daphnia population density (11,12) or even population crashes (17) might result in disruptions of aquatic food webs, as daphnids play important roles as main phytoplankton grazers and as a major food of planktivorous fish (27).…”
mentioning
confidence: 99%
“…D. dentifera hosts a variety of parasites and pathogens (Ebert 2005), and experiences seasonal epidemics of the fungal yeast parasite Metschnikowia bicuspidata (Metschnikoff ). The size of seasonal epidemics depends on a number of factors (e.g., Hall et al 2006, Duffy and Sivars-Becker 2007, Duffy and Hall 2008, Overholt et al 2012) that drive significant variation in host and disease dynamics. Hosts consume infectious spores during feeding and die 10-14 days post-infection, releasing spores back into the water column (Green 1974).…”
Section: Methodsmentioning
confidence: 99%
“…In a bacteriaprotozoa-mosquito larvae food web, predation by mosquito larvae on protozoa had stronger effects at the warmer site than the cooler site, perhaps because the mosquito larvae fed more at the warmer site (D. Hoekman, unpublished manuscript). Though both topdown and bottom-up effects could increase with metabolism, the effect of temperature on the relative importance of top-down and bottom-up effects is expected to depend on multiple other factors, including thermal scaling, body size, and thermal adaptations of predators, prey, and basal resources (Hall et al 2006).…”
Section: Introductionmentioning
confidence: 99%